Internalisasi Karakter Religius Melalui Tradisi Pembacaan Surah Al-Fatihah: Studi Living Qur’an Pada Santri Magrib Mengaji - Rahmat Rifai Lubis; Latifah Hanum; Masruroh Lubis (Hikmah, 2022)
This study aims to analyze the internalization of religious character through the tradition of reading surah Al-Fatihah. This research focuses on three things, namely background, tradition, and the process of character internalization. This research was carried out at the Maghrib Study Program Assembly at the Muslim Mosque on Jalan Bromo. The research method used is qualitative research with a phenomenological approach. The data sources in this study are divided into two, namely research informants which include the teacher and santri magrib recitation programs and the library which covers the learning outcomes of students and the results of previous research. Data collection techniques using observation, interviews, and documentation studies. Data analysis uses miles and Huberman techniques, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the background of the emergence of short programs was based on religious, philosophical and pedagogical considerations. This tradition is carried out to form the character of Monotheism, Worship, Ta'awun, Blessing. Traditions carried out at the time before learning, addressed to people who are sick and get pleasure. The internalization process is carried out through the value transformation stage, the value transaction stage, and the transinternalization stage.